2016
DOI: 10.4269/ajtmh.15-0913
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Q Fever, Brucellosis, and Bluetongue in Selected Provinces in Lao People's Democratic Republic

Abstract: Abstract. This study has determined the proportional seropositivity of two zoonotic diseases, Q fever and brucellosis, and bluetongue virus (BTV) which is nonzoonotic, in five provinces of Lao People's Democratic Republic (PDR) (Loungphabang, Luangnumtha, Xayaboury, Xiengkhouang, and Champasak, and Vientiane Province and Vientiane capital). A total of 1,089 samples from buffalo, cattle, pigs, and goats were tested, with seropositivity of BTV (96.7%), Q fever (1.2%), and brucellosis (0.3%). The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…This rate is higher than the 3.53% reported in yaks in Qinghai Province, China [7], and 9.3% among the domestic ruminants in Northern Kerala, India [3]. However, it is lower than the 27.9% prevalence reported in small ruminants in Nepal [2], 33.13% in sheep and goat in South Bengal [9], 43.68% in ruminants in Jharkhand, India [10], 45.20% among domestic ruminants in the highlands of Nepal [11], and 96.7% in buffaloes and cattle in selected provinces in Lao People's Democratic Republic [12]. Many factors, including the diagnostic methods, climatic conditions, geographical conditions, species/breeds, sample sizes, and sanitation, may contribute to such differences.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher than the 3.53% reported in yaks in Qinghai Province, China [7], and 9.3% among the domestic ruminants in Northern Kerala, India [3]. However, it is lower than the 27.9% prevalence reported in small ruminants in Nepal [2], 33.13% in sheep and goat in South Bengal [9], 43.68% in ruminants in Jharkhand, India [10], 45.20% among domestic ruminants in the highlands of Nepal [11], and 96.7% in buffaloes and cattle in selected provinces in Lao People's Democratic Republic [12]. Many factors, including the diagnostic methods, climatic conditions, geographical conditions, species/breeds, sample sizes, and sanitation, may contribute to such differences.…”
Section: Discussionmentioning
confidence: 99%
“…C . burnetii seroprevalence studies in Laos have revealed the pathogen is not widely distributed in cattle, despite the likelihood of an epidemiological hotspot in the Thailand-bordered province of Xayaboury [ 12 , 13 ]. Thailand is a significant trading partner with Laos, and C .…”
Section: Introductionmentioning
confidence: 99%
“…Horton et al (2014) found that seropositivity rates of Q fever by ELISA were 4% (6/153) in buffaloes, 8% (14/174) in sheep and 70% (7/10) in camels. In another study (Douangngeun et al, 2016) found that in 526 cattle blood serum taken for serological screening of abort agents in different animal species by ELISA, only 13 (1.2%) cattle blood serums were detected as seropositive for Q fever while 426 pigs, 130 buffaloes, and 6 goat blood serum were all negative. In a recent study in which Q fever disease was searched serologically in sheep and buffaloes in Iran (Karami Mirazizi et al, 2017), 47 of 137 (34.3%) goat serum were detected as positive while all of 135 buffalo blood serum samples tested were found to be seronegative.…”
Section: Discussionmentioning
confidence: 97%
“…A large number of studies have been conducted in different countries to determine the Q Fever disease in various animal species (Horton et al, 2014;Douangngeun et al, 2016;Karami et al, 2017;Pradeep et al, 2017). Likewise, there are serological and molecular studies related to Q Fever in sheep, goats, cattle and humans in our country (Karaca et al, 2009;Gunaydın et al, 2014;Can et al, 2015; Cetinkol et al, 2017; Cıkman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation